2019
DOI: 10.1139/cjfas-2017-0389
|View full text |Cite
|
Sign up to set email alerts
|

Movement types of an Arctic benthic fish, shorthorn sculpin (Myoxocephalus scorpius), during open-water periods in response to biotic and abiotic factors

Abstract: Shorthorn sculpin (Myoxocephalus scorpius) are among the most numerous consumers in the Arctic nearshore marine habitats. Despite this, little is known about their movement ecology or predator–prey interactions, particularly with Arctic cod (Boreogadus saida), an important forage fish in the Arctic. Using acoustic telemetry, the movements of tagged sculpin and cod were quantified based on specific locations using a Vemco positioning system during open water when both species were present in the near shore. Mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Spatial shifts in the distribution of marine fishes occurs at multiple spatial scales ranging from small-scale habitat shifts (Moulton et al, 2017;Landry et al, 2018;Rooker et al, 2018) to large-scale journeys across ocean basins (Galuardi et al, 2010;Block et al, 2011;Kraus et al, 2011). Migratory patterns of pelagic fishes and other marine vertebrates at the basin scale (i.e., transoceanic) are often influenced by both intrinsic and external factors, including spatial shifts in prey quantity/quality, thermal tolerance/sea surface temperatures, and other incentives related to reproduction and/or energetics (Secor, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Spatial shifts in the distribution of marine fishes occurs at multiple spatial scales ranging from small-scale habitat shifts (Moulton et al, 2017;Landry et al, 2018;Rooker et al, 2018) to large-scale journeys across ocean basins (Galuardi et al, 2010;Block et al, 2011;Kraus et al, 2011). Migratory patterns of pelagic fishes and other marine vertebrates at the basin scale (i.e., transoceanic) are often influenced by both intrinsic and external factors, including spatial shifts in prey quantity/quality, thermal tolerance/sea surface temperatures, and other incentives related to reproduction and/or energetics (Secor, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…1), including a special two-part issue in the Journal of International Wildlife Law and Policy (VanderZwaag et al 2013). The approach improved the scope of OTN research and is reflected in many of the studies described in this special issue, for example using oceanographic data to understand shorthorn sculpin (Myoxocephalus scorpius) movements in the Arctic (Landry et al 2019) and temperature to study migrating Pacific salmon (Middleton et al 2018).…”
Section: Special Issue Overview Of Contributionsmentioning
confidence: 99%
“…For this special issue, two of the OTN Arctic papers focus on shorthorn sculpin, a common nearshore benthic fish found throughout the Arctic and thought to play a key role in integrating benthic and pelagic food webs (McMeans et al 2015), but whose movement ecology has been largely unknown. Working in the High Arctic and using acoustic telemetry and the Vemco positioning system (which provided high-resolution location and movement data), Landry et al (2019) demonstrated that these Arctic fish displayed three unique movement types that had analogues in temperate benthic fish. These movement types (foraging, feeding, and large transit movements) were influenced by the presence of other fish, temperature, and sea ice, suggesting that changes in climate will have considerable implications for Arctic fishes.…”
Section: Arctic Otnmentioning
confidence: 99%